Mucosal involvement in bullous and cicatricial pemphigoid. A clinical and immunopathological study. - Venning, V; Frith, P; Bron, A; Millard, P; Wojnarowska, F (1988)
Thirty-six patients with bullous pemphigoid (BP) and 15 with cicatricial pemphigoid (CP) were studied for evidence of mucosal involvement both clinically and by direct immunofluorescence. Twenty-one patients with BP and all those with CP had lesions of the mucous membranes. Eighteen patients with BP and 14 patients with CP had involvement of the oral mucosa. Lesions of the eyes, nose, pharynx, vulva and urethra also occurred in both groups. The lesions tended to be more widespread in CP patients. Twenty-one patients with BP and 14 with CP were examined by an ophthalmologist. Fine scarring of the tarsal conjunctiva was found in both groups, but also in elderly controls. However, symblepharon occurred in one patient with BP as well as in three patients with CP, but was not seen in a group of 20 controls. Direct immunofluorescence (IF) studies showed linear deposition of IgG or C3 or both in the basement membrane zone of the skin, oral mucosa and conjunctival mucosa in both groups. The frequency of positive immunofluorescence was higher in the conjunctiva than in the lip mucosa or skin in both BP and CP patients. The significance of these findings and the relationship between BP and CP is discussed.